Burmese days - Orwell, George, 1903-1950. (London : Penguin Books, 2009)
James Flory, one of a very few Englishmen living in Burma to appreciate the Indian culture and people, must find the moral courage to nominate his friend, Dr. Veraswami, for membership in the previously all-white European Club.
Adult.
Adult
Keywords: Burma -- History -- Fiction; Burma -- Race relations -- Fiction; Burma -- History -- Fiction; Burma -- Race relations -- Fiction